High-performance supercapacitors using graphene/polyaniline composites deposited on kitchen sponge. (26th January 2015) - Moussa, Mahmoud; El-Kady, Maher F; Wang, Hao; Michimore, Andrew; Zhou, Qinqin; Xu, Jian; Majeswki, Peter; Ma, Jun
Abstract: We in this study used a commercial grade kitchen sponge as the scaffold where both graphene platelets (GnPs) and polyaniline (PANi) nanorods were deposited. The high electrical conductivity of GnPs (1460 S cm −1 ) enhances the pseudo-capacitive performance of PANi grown vertically on the GnPs basal planes; the interconnected pores of the sponge provide sufficient inner surface between the GnPs/PANi composite and the electrolyte, which thus facilitates ion diffusion during charge and discharge processes. When the composite electrode was used to build a supercapacitor with two-electrode configuration, it exhibited a specific capacitance of 965.3 F g −1 at a scan rate of 10 mV s −1 in 1.0 M H2 SO4 solution. In addition, the composite Nyquist plot showed no semicircle at high frequency corresponding to a low equivalent series resistance of 0.35 Ω . At 100 mV s −1, the supercapacitor demonstrated an energy density of 34.5 Wh kg −1 and a power density of 12.4 kW kg −1 based on the total mass of the active materials on both electrodes. To demonstrate the performance, we built an array consisting of three cells connected in series, which lit up a red light emitting diode for five minutes. This simple method holds promise for high-performance yet low-cost electrodes for supercapacitors.